A novel theoretical approach to predict the interannual variability of sulfur in Mercury’s exosphere and subsurface - Verkercke, S.; Chaufray, J. Y.; Leblanc, F.; Georgiou, A.; Phillips, M. S.; Munaretto, G.; Lewis, J.; Ricketts, A.; Morrissey, L. (Frontiers in Astronomy and Space Sciences, 2025)
The surfaces of airless bodies are constantly weathered by ions, meteoroids, and radiation, leading to the ejection of surface atoms to form a tenuous, collisionless atmosphere around the body. In the case of Mercury, its high surface temperatures can also lead to thermal desorption (TD) of atoms. Since its discovery approximately 50 years ago, Mercury’s exosphere has been extensively observed by both ground-based and space-borne telescopes. The MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft operated 4 years in orbit around Mercury and allowed for the surface composition species to be inferred, notably including sulfur (S). Sulfur was, however, never observed in Mercury’s exosphere. In this study, we use a unique theoretical approach that combines modeling methods across different dimensional scales to understand the presence of sulfur on Mercury. Using a 3D exospheric global model with a Monte-Carlo test-particles approach and accounting for species diffusion in the first meter of Mercury’s regolith, this study aims to provide the first global prediction of the interannual variability of neutral sulfur density in both Mercury’s exosphere and subsurface. Our model predicts the formation of subsurface reservoirs at different depths according to the planetary longitude, with an equatorial reservoir peak location at ∼ 21 cm and ∼ 8 cm below the surface at the hot and cold poles, respectively. Cold longitudes are also predicted to accumulate 6.7 times more sulfur than the hot longitudes. Regarding the exosphere, the larger abundance of sulfur at the cold longitudes induces a local enhancement of the exospheric density around aphelion. The calcium surface abundance is predicted to influence the sulfur adsorption location, leading to a sulfur content enhancement in the vicinity of the −90°E longitude. Our results could be beneficial for optimizing the planning and aiding the analysis and interpretation of future observations of Mercury’s exosphere by BepiColombo.